Reticulate Evolution in AA-Genome Wild Rice in Australia - Hasan, Sharmin; Furtado, Agnelo; Henry, Robert (Frontiers in Plant Science, 2022)
The wild rice gene pool, i.e., AA-genome, in Australia is geographically and genetically distinct from that in Asia. Two distinct taxa are found growing together in northern Australia, Oryza meridionalis (including annual and perennial forms) and an Oryza rufipogon like taxa that have been shown to have a chloroplast genome sequence that is closer to that of O. meridionalis than to O. rufipogon from Asia. Rare plants of intermediate morphology have been observed in the wild despite a reported reproductive barrier between these two species. We now report the resequencing of plants from 26 populations including both taxa and putative hybrids. A comparison of chloroplast and nuclear genome sequences indicated re-combinations that demonstrated hybridisation in both directions. Individuals with intermediate morphology had high nuclear genome heterozygosity consistent with a hybrid origin. An examination of specific genes (e.g., starch biosynthesis genes) revealed the presence of heterozygotes with alleles from both parents suggesting that some wild plants were early generation hybrids. These plants may have low cross-fertility preserving the continuation of the two distinct species. Repeated backcrossing of these rare hybrids to one parent would explain the plants exhibiting chloroplast capture. These observations suggest that reticulate evolution is continuing in wild Oryza populations and may have been a key process in rice evolution and domestication.